Authentication scheme using unique identification method with homomorphic encryption in Mobile Cloud Computing - Lim, Tsu Chean; Ponnusamy, Vasaki; Sulaiman, Mohamed Fati (2018)
The purpose of this project is to design and implement a framework that employs unique authentication method that relies on third party identification which is required to accurately identify and authenticate legitimate user in order to reduce the risk of disclosing confidential data to unauthorized party in Mobile Cloud Computing, MCC. Cloud computing is a service provided for user to store and process their data online instead of local device. Mobile Cloud computing which is an extension of the cloud computing service allows user to remotely access their data and services that are being uploaded to the cloud beforehand in any place and any time as long as they have internet connection in their personal mobile device. Throughout the period of the mobile cloud computing era, the security has always been a concern and post as a formidable challenge even for experienced security specialist. Moreover, encryption method such as RSA and Diffie Hellman cryptosystem proven to be useless against the attacks launched by quantum computer. Hence, Homomorphic Signature scheme is introduced along with the Identity Management (IDM) server into the mobile cloud computing in order to address this issue by applying implicit authentication method to differentiate between the genuine and non-genuine user which allows system to authenticate the clients accurately. The details of the framework will be further explained later in this paper, where the user will be authenticated with IDM as medium and no password is used throughout the authentication process, allowing the client to be safely authenticated at the end of the process.